2001
DOI: 10.1109/20.951142
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermomagnetic properties of new FeCo-based nanocrystalline ferromagnets

Abstract: FeCo-based ferromagnetic alloys (HIT-PERM variants) of composition Fe 44 5 Co 44 5 Zr 7 B 4 , Fe 44 Co 44 Zr 5 7 B 3 3 Ta 2 Cu 1 , Fe 44 Co 44 Zr 5 7 B 3 3 Mo 2 Cu 1 , and Fe 37 2 Co 30 8 Zr 7 B 4 Cu 1 were prepared by melt-spinning amorphous precursors, followed by nanocrystallization. Samples were characterized using vibrating sample magnetometry (VSM), x-ray diffraction (XRD), and differential scanning calorimetry (DSC). VSM was used to measure magnetization vs. temperature from 370-1260 K. Magnetic data sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…1a) and a linear dependence with two slopes can be established between them. The T c of the as-cast amorphous phase in these alloys is significantly lower than the observed for similar Hitperm [3] or Finemet [18] Mo-free alloys, as expected from the known effect of Mo addition on the Curie temperature of the alloy [8]. In fact the Fe 79 Mo 8 Cu 1 B 12 alloy is paramagnetic at room temperature [11].…”
Section: Devitrification Processmentioning
confidence: 48%
See 1 more Smart Citation
“…1a) and a linear dependence with two slopes can be established between them. The T c of the as-cast amorphous phase in these alloys is significantly lower than the observed for similar Hitperm [3] or Finemet [18] Mo-free alloys, as expected from the known effect of Mo addition on the Curie temperature of the alloy [8]. In fact the Fe 79 Mo 8 Cu 1 B 12 alloy is paramagnetic at room temperature [11].…”
Section: Devitrification Processmentioning
confidence: 48%
“…Moreover, due to their small diffusivity in the amorphous phase, they accumulate at the crystal-matrix interface and constrain the growth of the crystalline phase to the nanocrystalline scale. Many studies on Hitperm FeCoZrB and FeCoNbB alloys have been reported [1][2][3][4][5] but, more recently, FeCoMoB alloys have been paid increasing attention [6]. Mo addition to Fe alloys delays the iron oxidation in this system and affects the thermal stability and magnetic properties of these amorphous alloys, with a significant lowering of the Curie temperature [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Another (Co 0.5 Fe 0.5 ) 88 Zr 7 B 4 Cu 1 alloy composition of interest has an Fe/Co ratio of two to one, with the maximum saturation magnetization for the nanocrystalline phase and smaller magnetostrictive losses. 13) That being said, the magnetostrictive contributions to the losses of (Co 0.5 Fe 0.5 ) 88 Zr 7 B 4 Cu 1 alloys are appreciable over the whole composition range due to the large values found in the nanocrystallites themselves.…”
Section: Alloy Designmentioning
confidence: 99%
“…Thermomagnetic measurements of the amorphous precursors to (Co 0.5 Fe 0.5 ) 88 Zr 7 B 4 Cu 1 show the magnetization of the amorphous phase persists until the primary crystallization temperature. 12,13) It is reasonable to assume that the orbital angular momentum of the transition metal atoms in the amorphous phase is effectively quenched and that only spin angular momentum (S) contributes to the moment, J . Hence, the thermomagnetic behavior of amorphous (Co 0.5 Fe 0.5 ) 88 Zr 7 B 4 Cu 1 can be fit to a spin only Brillouin function (J = ±S), yielding values for the internal field and magnetic moment.…”
Section: Magnetic Popertiesmentioning
confidence: 99%
See 1 more Smart Citation